A retrospective audit into the morbidity and mortality of open abdominal aortic aneurysm repair at Groote Schuur Hospital, Cape Town - Mhlanga, Gugulethu Tsakani Jenny (Department of Anaesthesia, 2017)
Background: Open AAA repair is a major, high risk surgery and is associated with significant morbidity and mortality. Current literature quotes an overall mortality of ruptured AAA at 85-90%, including those who do not reach the operating theatre. Mortality of elective AAA repairs is 4-8%. Many patients presenting with abdominal aortic aneurysms are elderly and have pre-existing medical conditions, therefore putting them at high risk for numerous post-operative complications, such as acute kidney injury, pulmonary and cardiac complications. These complications lead to potentially increased ICU and hospital stays. Objectives: To the author's knowledge, an audit into the morbidity and mortality at Groote Schuur Hospital has not yet been formally performed. Such a retrospective audit will be useful in establishing where this hospital stands in terms of mortality, as compared with published data from international centres. In terms of morbidity, this research focused on the development of acute kidney injury following AAA repair. Methods: The study design was an observational retrospective file audit, of both emergency and elective open abdominal aortic aneurysm repairs. 90 case reports of operations performed between October 2006 and December 2014 were analysed. The primary outcome measure was the incidence and causes of perioperative (30-day) mortality. The secondary outcome measure was the incidence of acute kidney injury and renal replacement therapy (RRT). We further analysed whether cross-clamp time and anatomical classification of the aneurysm had any effect on the subsequent need for RRT, utilising the Mann-Whitney test. Results: Of the 90 patients, 76.7% were male (n=69). The study population had a mean age of 64.9 years. Overall perioperative (30-day) mortality of both emergency and elective cases was 15 out of 90 cases (16.6%); the mortality for emergency cases was 12 out 31 (38.7%), as compared to 3/59 (5.1%). Seventeen patients (18.9%) developed KDIGO stage 3 AKI, and RRT was instituted in 12 cases (13.3% of all patients); seven patients survived, and no patients were dialysis-dependent on hospital discharge. AKI was not significantly associated with abdominal aortic cross-clamp time (46 minutes vs. 38 minutes, p=0.9021), but was significantly associated with anatomical classification of the aneurysm (supra-/juxtarenal vs. infrarenal, p=0.037). Conclusions: In comparison with research from international centres, this study population was predominantly male, with a similar age profile to that quoted. The bulk of the perioperative mortality was from emergency AAA repairs, with the mortality associated with elective open AAA surgical repair being within the ranges quoted in international literature. Of the patients who received RRT, there was a mortality of 41.6%. There were many limitations in this study, as the population analysed was extremely heterogeneous, owing to the small sample size. There is great potential for further research, especially into the outcomes of open versus endovascular repairs of AAAs.